MARKETING COMMUNICATION STRATEGIES IN ISLAMIC EDUCATIONAL INSTITUTION: BETWEEN DA’WAH AND BRANDING - Abdul Haris; Siti Salwa Binti Bahari; Selamat Riadi; Fauji Wikanda (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This article discusses the marketing communication strategies implemented by Islamic educational institutions in the context of their dual role as a means of da'wah (Islamic outreach) and an effort to build the institution's image (branding). In an era of increasingly fierce educational competition, Islamic educational institutions are required to adapt to modern communication developments without abandoning the Islamic values ​​that define their identity. This research uses a qualitative descriptive approach, incorporating literature studies and observations of marketing communication practices in several Islamic educational institutions. The results indicate that effective marketing communication strategies in Islamic educational institutions must be based on the principles of honesty, trustworthiness, and brotherhood, and must be able to package da'wah messages creatively and relevantly to community needs. Institutional branding is built not only through promotion but also through the quality of education, teacher exemplary behavior, and an Islamic environment. Thus, marketing communication in Islamic educational institutions serves a dual function: as a da'wah medium that spreads Islamic values, and as a means of building public trust and loyalty to the institution.